Rosmarinic Acid Inhibits Mitochondrial Damage by Alleviating Unfolded Protein Response - Cai, Guoen; Lin, Fabin; Wu, Dihang; Lin, Chenxin; Chen, Huiyun; Wei, Yicong; Weng, Huidan; Chen, Zhiting; Wu, Minxia; Huang, En; Ye, Zucheng; Ye, Qinyong (Frontiers in Pharmacology, 2022)
Mitochondria are essential organelles that perform important roles in cell biologies such as ATP synthesis, metabolic regulation, immunomodulatory, and apoptosis. Parkinson's disease (PD) is connected with mitochondrial neuronal damage related to mitochondrial unfolded protein response (mtUPR). Rosmarinic acid (RA) is a naturally occurring hydroxylated polyphenolic chemical found in the Boraginaceae and the Labiatae subfamily Nepetoideae. This study looked into RA's protective effect against mitochondrial loss in the substantia nigra (SN) caused by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), the underlying mechanism associated with the mtUPR. Pretreatment with RA reduced motor impairments and dopaminergic neuronal degeneration in the SN of a mouse model injected with MPTP. Pretreatment of SH-SY5Y cells from cell viability loss, morphological damage, and oxidative stress. Furthermore, RA pre-injection controlled the mtUPR, lowered the expression of HSPA9, HSPE1, CLPP LONP1, and SIRT 4, and protected the MPTP-mice SH-SY5Y cells from mitochondrial failure. The findings imply that RA can prevent Parkinson's disease by preventing mitochondrial damage in dopaminergic neurons in Parkinson's disease via increasing mitochondrial unfolded protein response.